2017
DOI: 10.1097/coc.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival in Patients Treated for a Lung Cancer Using Self-Evaluated Symptoms Reported Through a Web Application

Abstract: Survival may be improved by early detection of relapse and early palliative care initiation by using sentinel-like Web-application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 15 publications
2
57
2
3
Order By: Relevance
“…A recent randomized controlled trial by Denis and colleagues has shown a significant median overall survival benefit of 5 months for lung cancer patients who were systematically telemonitored using a mobile app based on patient-reported data and using the dynamics of patients’ clinical symptoms for risk stratification and individualized follow-up [ 18 , 35 ]. Similar approaches have successfully been used in the management of toxicities related to head and neck cancer treatment: computerized screening could facilitate the identification of treatment-related toxicities, and telepractice apps or videoconferencing could assist in the delivery of intensive home-based dysphagia therapy [ 24 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled trial by Denis and colleagues has shown a significant median overall survival benefit of 5 months for lung cancer patients who were systematically telemonitored using a mobile app based on patient-reported data and using the dynamics of patients’ clinical symptoms for risk stratification and individualized follow-up [ 18 , 35 ]. Similar approaches have successfully been used in the management of toxicities related to head and neck cancer treatment: computerized screening could facilitate the identification of treatment-related toxicities, and telepractice apps or videoconferencing could assist in the delivery of intensive home-based dysphagia therapy [ 24 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was overall survival after 2 years of follow-up, which was selected based on prior pilot research. 3 Survival data were gathered from patient follow-up by blinded investigators. After a preplanned interim analysis in January 2016 in which a significant survival improvement was observed, the data and safety monitoring committee mandated cessation of recruitment and crossover of control patients to the intervention.…”
mentioning
confidence: 99%
“…The multidimensional platform and its capabilities to combine electronic Patient-Reported Outcomes (PROs) with circadian rhythm monitoring and body weight measures meet the expectations of the American Society for Clinical Oncology, regarding the future of e-Health technologies in cancer medicine [52]. Thus, the weekly transmission of electronic PROs significantly improved overall survival in two randomized trials conducted in cancer patients, indicating this information might elicit initially unplanned interventions and/or modify patient's engagement with an oncologic benefit equivalent to that of the addition of an active drug [53,54]. The PiCADo platform provides a novel framework for the further integration of circadian rhythms and other parameters into proactive timely care interventions and the ready assessment of their efficacy.…”
Section: Discussionmentioning
confidence: 99%